A09 Ran-translation products are selectively taken up by a microglia cell line and induce an inflammatory response via the NLRP3 inflammasome pathway. (12th September 2022) - Jamin, Raul Nicolás; Dansokho, Cira; Heneka, Michael T; Weydt, Patrick
Abstract : Repeat-Associated Non-ATG-induced (RAN) translation is an unconventional mechanism of translation found in various neurodegenerative diseases. In Huntington's disease this mechanism produces four homopolymeric peptides, poly-Alanine, -Cysteine, -Leucine and -Serine. These accumulate in neurons and in the CSF of affected individuals and are associated with increased neuronal death and white matter loss. The extent to which they contribute to neuroinflammation remains unknown. Here we assess the capability of HD-RAN peptides to acts as DAMPS and induce an inflammatory response via activation of the NLRP3 inflammasome pathway in the J774.2 cell line. We demonstrate the selective and time-peptide dependent uptake of the proteins by the J774.2 cells, differentially inhibitable by the actin polymerization inhibitor Cytochalasin D, as well as a peptide-dependent capability of these cells to degrade the different peptides after uptake. We furthermore demonstrate an activation of the NLRP3 inflammasome in J774.2 through treatment with RAN peptides via Western Blotting and IL-1ß Elisa as well as the possibility to inhibit the inflammatory response with the selective NLRP3 inhibitors MCC950 and IFM-compound. We additionally show that the inflammatory response is not limited to the NLRP3 inflammasome, but extends to other inflammatory pathways. This work implicates RAN-peptides as a driver of neuroinflammation in HD via the NLRP3 inflammasome and other pathways that can be targeted pharmacologically.